(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This paper discusses the emerging debate concerning the concept of Cognitive Liberty and its connection with human rights. Therefore, considering how recent developments of neurosciences are granting us an increasing ability to monitor and influence mental processes, this article aims to provide a clear definition of Cognitive Liberty understood as a necessary condition to all other freedoms that cannot be reduced to existing rights. In this regard, after presenting the most important positions on the issue, we introduce our point of view, according to which Cognitive Liberty allows us to lay the groundwork for building new neuro-related Human Rights.